2009
DOI: 10.1016/j.niox.2009.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Plasma nitrate/nitrite levels are unchanged after long-term aerobic exercise training in older adults

Abstract: Reduced nitric oxide (NO) production and bioactivity is a major contributor to endothelial dysfunction. Animal data suggests that improvements in endothelial function in response to aerobic exercise training may depend on the duration of the training program. However, no studies have examined changes in NO (as assessed by the major NO metabolites, nitrate and nitrite, NOx) after long-term training in humans. In addition, aging may impair the ability of the vasculature to increase NO with exercise. Thus, we det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 38 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…It has been long recognized that supplementation of L-Arg, the endogenous physiological precursor of NO, improves endothelial vasodilator function of coronary and peripheral arteries (23). More recently, L-Arg supplementation was also shown to reduce moderate-intensity exercise-induced oxidative stress and enhance high-intensity exercise tolerance (1,5). In this study, we investigated whether L-Arg supplementation attenuates endurance training and an exhaustive exercise-induced oxidative stress using rat models.…”
Section: Discussionmentioning
confidence: 95%
“…It has been long recognized that supplementation of L-Arg, the endogenous physiological precursor of NO, improves endothelial vasodilator function of coronary and peripheral arteries (23). More recently, L-Arg supplementation was also shown to reduce moderate-intensity exercise-induced oxidative stress and enhance high-intensity exercise tolerance (1,5). In this study, we investigated whether L-Arg supplementation attenuates endurance training and an exhaustive exercise-induced oxidative stress using rat models.…”
Section: Discussionmentioning
confidence: 95%
“…However, the responses to longer-term training ( ≥ 16 wk) seem to be more variable. In a group of older men and women, 24 wk of exercise training did not improve plasma NOx levels [ 1 ] . Given the extremely long duration of training in the present study, the lack of association between activity level and plasma NOx levels may be less surprising.…”
mentioning
confidence: 86%
“…However, our plasma NOx measurement is an assessment of NO bioavailability as opposed to a measurement of endothelial function. Although reduced NO bioavailability is one mechanism thought to cause endothelial dysfunction [ 1 ] , impairments in endothelial function can occur without decreases in NOx levels. For example, an earlier study found that atherosclerotic rabbits had higher plasma NO levels, as determined by quantifying nitrosyl compounds in blood, but impaired endothelium-dependent vasodilation, compared to control rabbits [ 25 ] .…”
mentioning
confidence: 99%
“…The good news is that these changes are not observed in lifelong physically active men. However, 24 weeks of aerobic training, increasing by 15%, failed to significantly increase venous NO metabolites and forearm flow mediated vasodilatation in older men and women (Brinkley et al 2009). Despite leg training, in the study of Brinkley et al (2009), forearm flow mediated vasodilatation should have been improved (Green et al 2004).…”
mentioning
confidence: 99%
“…However, 24 weeks of aerobic training, increasing by 15%, failed to significantly increase venous NO metabolites and forearm flow mediated vasodilatation in older men and women (Brinkley et al 2009). Despite leg training, in the study of Brinkley et al (2009), forearm flow mediated vasodilatation should have been improved (Green et al 2004). In fact, Hambrecht et al (1998) found increased acetylcholine‐induced blood flow in the femoral artery after 24 weeks of aerobic training in chronic heart failure patients (mean age = 56 years).…”
mentioning
confidence: 99%